Headache associated with compression of the third cranial nerve by an aneurysm of the posterior communicating artery - Valença, Marcelo M.; Silva, Joacil Carlos da; Barbosa, Marcos; Valença, Martina F.; Almeida, Laryssa Azevedo; Oliveira, Maria Carolina M.; França, Cássia L. S.; Oliveira, Raíza R. B.; Soares, Míriam C.; Nunes, Eduardo C.; Costa, Rafael G.; Farias, Helysândia S. S.; et al. (Headache Medicine, 2014)
Continuous unilateral pain in the orbital area may be a sign of an intracranial structural lesion. We report a case of a 64-yearold woman with continuous headache of moderate intensity at the region of the left eye bulb. There was a complete paralysis of the left third oculomotor nerve. The patient was admitted with headache, vomiting, palpebral ptosis, divergent strabismus of the left eye, diplopia when looking to the left, upwards and downwards and paralytic mydriasis on the left. The Angiography revealed a saccular aneurysm dilation in the internal carotid artery with origin at the origin of the left posterior communicating artery. A microsurgery was performed on the aneurysm of the left internal carotid artery and the aneurysm was occluded by clipping. On four months follow up the patient is asymptomatic, with a complete recovery of the third nerve palsy. There is still much controversy about microsurgical and endovascular therapy in cerebral aneurysms, this case represents the good outcome in a patient with paralysis of the oculomotor nerve after microsurgery occlusion of a posterior communicating aneurysm. In conclusion, all patients with a continuo pain in the orbital area need to be evaluated by angiography in order to display a intracranial aneurysm.